Neutrophil extracellular trap formation and gene programs distinguish TST/IGRA sensitization outcomes among Mycobacterium tuberculosis exposed persons living with HIV. - Elouise E Kroon; Wilian Correa-Macedo; Rachel Evans; Allison Seeger; Lize Engelbrecht; Jurgen A Kriel; Ben Loos; Naomi Okugbeni; Marianna Orlova; Pauline Cassart; Craig J Kinnear; Gerard C Tromp; et al. (PLoS Genetics)
Persons living with HIV (PLWH) have an increased risk for tuberculosis (TB). After prolonged and repeated exposure, some PLWH never develop TB and show no evidence of immune sensitization to Mycobacterium tuberculosis (Mtb) as defined by persistently negative tuberculin skin tests (TST) and interferon gamma release assays (IGRA). This group has been identified and defined as HIV+ persistently TB, tuberculin and IGRA negative (HITTIN). To investigate potential innate mechanisms unique to individuals with the HITTIN phenotype we compared their neutrophil Mtb infection response to that of PLWH, with no TB history, but who test persistently IGRA positive, and tuberculin positive (HIT). Neutrophil samples from 17 HITTIN (PMNHITTIN) and 11 HIT (PMNHIT) were isolated and infected with Mtb H37Rv for 1h and 6h. RNA was extracted and used for RNAseq analysis. Since there was no significant differential transcriptional response at 1h between infected PMNHITTIN and PMNHIT, we focused on the 6h timepoint. When compared to uninfected PMN, PMNHITTIN displayed 3106 significantly upregulated and 3548 significantly downregulated differentially expressed genes (DEGs) (absolute cutoff of a log2FC of 0.2, FDR < 0.05) whereas PMNHIT demonstrated 3816 significantly upregulated and 3794 significantly downregulated DEGs following 6h Mtb infection. Contrasting the log2FC 6h infection response to Mtb from PMNHITTIN against PMNHIT, 2285 genes showed significant differential response between the two groups. Overall PMNHITTIN had a lower fold change response to Mtb infection compared to PMNHIT. According to pathway enrichment, Apoptosis and NETosis were differentially regulated between HITTIN and HIT PMN responses after 6h Mtb infection. To corroborate the blunted NETosis transcriptional response measured among HITTIN, fluorescence microscopy revealed relatively lower neutrophil extracellular trap formation and cell loss in PMNHITTIN compared to PMNHIT, showing that PMNHITTIN have a distinct response to Mtb.